Digital sexual literacy: the potential for online spaces to support sexual literacy among young people - Power, Jennifer; James, Alexandra; Waling, Andrea; Pym, Tinonee; Lim, Gene (Frontiers in Education, 2024)
Health literacy is defined as the capacity, resources and insight to seek information, ask critical questions and be an advocate for one's health. Sexual literacy is framed in similar terms, relating to the capacity to navigate emotionally and physically safe sexual encounters and to hold a critical and assertive stance on relationship dynamics, gender and consent. In this paper, we present findings from a qualitative study that explored young people's use of the internet to develop sexual literacy.In-depth interviews were conducted with 22 young people (aged 18-25). Interviews explored the ways in which young people participate in online spaces to learn about sex, relationships, bodies and other aspects of sexual health. Data were analysed using qualitative, inductive thematic coding techniques.Young people described learning about sexual health online as a process of exploring ideas, topics or experiences (going down 'rabbit holes'). It was rarely the case that young people searched for specific information. Young people described engaging with multiple sources of content and multiple people online to learn about relationships or sex. This was often personal. Young people wanted to understand their own experiences and hear stories from people with similar experiences. Engaging with multiple sources, stories and people enabled critical reflection and peer-based learning.[Type here] Building sexual health literacy is not simply about providing young people with sexual health information. Rather, it is about supporting young people to develop critical insight and capacity to reflect deeply on experiences and issues that affect their sexual relationships. The online environment supports sexual literacy as it enables critical inquiry, access to multiple perspectives, peer connection and personal reflection.